Hand Reconstruction Using Anterolateral Thigh Free Flap by Terminal Perforator-to-Digital Artery Anastomosis: Retrospective Analysis - Kim, Jin Soo; Lee, Ho Hyung; Koh, Sung Hoon; Lee, Dong Chul; Roh, Si Young; Lee, Kyung Jin (Archives of Plastic Surgery, 2024)
This study aimed to analyze cases of anterolateral thigh (ALT) free flap used for hand reconstruction with terminal perforator-to-digital artery anastomosis. Patients who underwent ALT free flap placement with terminal perforator-to-digital artery anastomosis for hand reconstruction between January 2011 and August 2021 were included. The number, length, and diameter of the perforators and veins, flap size, and operative time were investigated through a retrospective review of charts and photographs. The occurrences of arterial thrombosis, venous thrombosis, arterial spasm, and flap necrosis were analyzed. In total, 50 patients were included in this study. The mean diameter and length of the perforators were 0.68 mm and 3.25 cm, respectively, and the mean number of veins anastomosed was 1.88, with a mean diameter of 0.54 mm. Complications included four cases of arterial thrombosis, one case of venous thrombosis, seven cases of partial necrosis, and one case of total flap failure. Regression analysis showed that a longer perforator was associated with arterial thrombosis whereas larger flap size and number of anastomosed veins were associated with partial necrosis (p < 0.05). The terminal perforator-to-digital artery anastomosis offers advantages in using compact free flaps with short pedicle lengths to cover small hand defects.
Keywords: microsurgical free flap; perforator flaps; hand injuries; reconstructive surgical procedures